Patricia Neal : An Unquiet Life - Shearer, Stephen Michael, 1951- (Book collections on Project MUSE., 2021)
" Major Motion Picture Adaptation Coming Soon The internationally acclaimed actress Patricia Neal (1926--2010) was a star on stage, film, and television for more than sixty years. On Broadway she appeared in such lauded productions as Lillian Hellman's Another Part of the Forest, winning the first Tony award. In Hollywood she starred opposite the likes of John Wayne, Paul Newman, John Garfield, and Gary Cooper in some thirty films. She is perhaps best known for her portrayal of Alma Brown in Hud, which earned her the 1963 Academy Award for Best Actress. But there was much more to Neal's life. She was born in Packard, Kentucky, though she spent most of her childhood in Knoxville, Tennessee. For a time, Neal became romantically involved with Gary Cooper, her married costar in The Fountainhead. In 1953, Neal wed famed children's author Roald Dahl, a match that would bring her five children and thirty years of dramatic ups and downs. At the pinnacle of her screen career, Neal suffered a series of strokes which left her in a coma for twenty-one days, and Variety even ran a headline erroneously stating that she had died. After a difficult recovery, Neal returned to film acting, earning a second Academy Award nomination for The Subject Was Roses (1968). She appeared in several television movie roles in the 1970s and 1980s and won a Golden Globe for Best Actress in a Dramatic TV Movie in 1971 for The Homecoming.Adapted as a major motion picture (filmed as An Unquiet Life) starring Hugh Bonneville, Keeley Hawes, and Sam Heughan, Patricia Neal: An Unquiet Life is the first critical biography detailing the actress's impressive film career and remarkable personal life. Author Stephen Michael Shearer conducted numerous interviews with Neal, her professional colleagues, and her intimate friends and was given access to the actress's personal papers. The result is an honest and comprehensive portrait of an accomplished woman who lived her life with determination and bravado."--